2013
DOI: 10.1371/journal.pone.0066076
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Roles for CBP and p300 on the RA-Mediated Expression of the Meiosis Commitment Gene Stra8 in Mouse Embryonic Stem Cells

Abstract: In mammalian germ cells, meiotic commitment requires the expression of Stimulated by retinoic acid gene 8 (Stra8), which is transcriptionally activated by retinoic acid (RA). However, little is known about the epigenetic mechanism by which RA induces Stra8 expression. Utilizing a chromatin immunoprecipitation assay (ChIP), we showed that RA increases histone acetylation at the Stra8 promoter in murine embryonic stem cells (ESCs), a model for germ cell differentiation. Furthermore, we explored whether two coreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Moreover, pull-down experiments with JARID-2 and EZH2 show that P300 interacts with PRC2 complex in undifferentiated conditions. These results are in agreement with those from previous studies that showed that P300 can act as a repressor independently of its acetyltransferase activity 25,26,42,43 . Possible posttranslational modifications such as a SUMO-dependent repression 25 or recruitment of other repressive components such as HDAC6 or HDAC1 26 remain to be studied.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, pull-down experiments with JARID-2 and EZH2 show that P300 interacts with PRC2 complex in undifferentiated conditions. These results are in agreement with those from previous studies that showed that P300 can act as a repressor independently of its acetyltransferase activity 25,26,42,43 . Possible posttranslational modifications such as a SUMO-dependent repression 25 or recruitment of other repressive components such as HDAC6 or HDAC1 26 remain to be studied.…”
Section: Discussionsupporting
confidence: 93%
“…1A, tracks 5, 6). These findings suggest that RA-related signals upregulate Meis2 expression via activation of an RAR/coactivator pathway in the proximal forelimb bud (Bajpe et al, 2013;Chen et al, 2013;Jin et al, 2011).…”
Section: Introductionmentioning
confidence: 77%
“…Furthermore, miR-630 mimic significantly decreased the expression of DDIT4, PARP3 and EP300 mRNA ( Figure 5d , upper panel) and of protein ( Figure 5e , left panel) in A549 cells, whereas anti-miR-630 increased their mRNA ( Figure 5d , lower panel) and protein ( Figure 5e , right panel) compared with scrambled siRNA, indicating DDIT4, PARP3 and EP300 as targets for miR-630. Next, we performed individual and combined silencing of three molecules in A549 by specific siRNA oligonucleotides 41 , 42 (also see http: // www.pnas.org/cgi/content/short/1016574108 ) to examine the effects of targeting DDIT4, PARP3 and EP300 by miR-630 on CIS-induced apoptosis. Compared with scrambled siRNA-transfected A549, where CIS exposure induced ~25.2% early apoptosis, silencing DDIT4, PARP3 or EP300 reduced 4.1% ( P =0.0435), 2.9% ( P =0.0476) and 6.8% ( P =0.0363) apoptosis, respectively; in particular, combined silencing of them reduced 10.7% apoptosis ( P =0.0085) ( Figures 5f and g and Supplementary Figure S8 ).…”
Section: Resultsmentioning
confidence: 99%